Penerapan Hipnosis 5 Jari terhadap Penurunan Tingkat Kecemasan pada Pasien Pre Op Batu Ureter di Ruangan Mawar RSUD Dr. Soehadi Prijonegoro Sragen - Gita Isnaini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Urinary Tract Stones (Urolithiasis) are a pathological condition due to hard masses such as stones that form along the urinary tract and can cause pain, bleeding, or infection in the urinary tract. The formation of stones is caused by urine being saturated with salts that can form stones or because the urine lacks materials that can inhibit stone formation, lack of urine production, and other idiopathic conditions. To find out the results of applying five finger hypnosis therapy to reduce anxiety levels in pre-operative ureteral stone patients in the Mawar Room at RSUD dr. Soehadi Prijonegoro Sragen. The type of research used is descriptive quantitative with survey methods. The research results showed that after being given 5 finger hypnosis to patients Mr.S and Mrs. K both respondents experienced a decrease in anxiety to mild anxiety level where Mr.S's anxiety level was 43 while Mrs. K anxiety level 44. Solid 5 finger hypnosis reduces anxiety levels in preoperative patients